PREVALENCE AND FACTORS ASSOCIATED WITH CONTRACEPTIVE USE AMONG KENYAN WOMEN AGED 15–49 YEARS. - Lunani, Laura L. (AIDS Behav, 2018)
Uptake of contraceptives is generally low in low-income settings. For women with HIV, contraception is a reliable and affordable method of minimizing vertical transmission. We investigated the factors that affect contraceptive use among Kenyan women using data collected during the Kenya Demographic & Health Survey (KDHS) of 2014. Data on contraceptive use were extracted from the 2014 KDHS database. Records of 31,079 Kenyan women of reproductive age (15–49 years) were analyzed. Frequencies were calculated; cross-tabulations and bivariate and multivariate analyses were conducted. Twelve thousand thirty-two women (39%) reported using a contraceptive method. Region, religion, education, number of living children, marital status, and prior testing for HIV were significantly associated with contraceptive use among women (P<.001). Social, economic, and demographic factors predict contraceptive use among Kenyan women and should be addressed in order to increase contraceptive uptake.